Morphology and taxonomy of a new species of Leptogorgia (Cnidaria: Octocorallia: Gorgoniidae) in Cocos Island National Park, Pacific Costa Rica - Breedy Shadid, Odalisca (2011)
Leptogorgia tricorata is a new shallow-water species found at 14–22 m depth at two rocky islets on the north side of Cocos Island National Park, Costa Rica. The branching pattern, the small size, bright yellow color, long spindles (up to 0.2 mm), and the occurrence of tentacular rods distinguish the new species from others in the genus. Gorgoniids are rare in shallow waters at Cocos Island. Including the new species there are only three species found so far in the region. Leptogorgia tricorata is described, illustrated, and compared with other similar species of the genus reported from the eastern Pacific.